O Papel da Direção de Inteligência Nacional (DINA) na Ditadura Chilena: para além da repressão (1974-1977) - Mendes, Clécio Ferreira (2016)
The objective of this thesis is to analyze the social function of Direction of National Intelligence, or DINA, agency that centered and organized the repressive apparatus of Chilean dictatorship from 1973 to 1977. In that sense, we sought to comprehend the idealization and the creation of DINA by the Military Joint of Government, under direct command of General Augusto Pinochet. The presented studies reveal that the Chilean dictatorship and DINA institute a wide movement of the right wing authoritarianism and antidemocratic against the social and political changes in course on that context and that they aimed to set up a project of bourgeois autocracy entitled “republic refoundation” and the establishment of a so-called “protected democracy”. The DINA as an unprecedented apparatus until 1974 performed roles beyond repression and suppression of social struggles or against dictatorship resistance. Its mission was the annihilation of the left and Marxism paving the way for the Chilean society standardization on the molds of a capitalist society. To guarantee the imposition of neoliberal reforms that transformed Chile